Sodium nitrate supplementation does not enhance performance of endurance athletes - Bescos, R.; Ferrer-Roca, V.; Galliea, P. A.; Roig, A.; Drobnic, F.; Sureda, A.; Martorell, M.; Cordova, A.; Tur, J. A.; Pons, A. (Medicine & Science in Sports & Exercise, 2012)
Purpose: Supplementation with inorganic nitrate has been suggested to be an ergogenic aid for athletes as nitric oxide donor. The purpose of this study was to determine whether ingestion of inorganic sodium nitrate benefits well-trained athletes performing a 40-min exercise test in laboratory conditions. In addition, we investigated the effect of this supplement on plasma levels of endothelin-1 (ET-1) and in nitrated proteins.